Aerobic and anaerobic biodegradability of accumulated solids in horizontal subsurface flow constructed wetlands. (April 2017) - Carballeira, T.; Ruiz, I.; Soto, M.
Abstract: This study reports the rate of total solids (TS) accumulation and hydraulic conductivity (HC) in five units of horizontal subsurface flow (HSSF) constructed wetlands (CWs), including unplanted and planted units with four different macrophytes ( Juncus effusus, Iris pseudacorus, Thypha latifolia L. and Phragmites australis ). Two monitoring campaigns were carried out at 17 (I) and 29 (II) months of operation, at surface loading rates of 2.5 and 4.7 g BOD5 m −2 d −1 respectively. Significant differences between units for TS density and most characteristics of accumulated solids were not found. On the contrary, significant differences existed between near inlet and outlet zones as well as between campaigns I and II. In aerobic conditions, approximately 35% of accumulated solids COD was biodegradable at maximum rates of 4.4–12.0 g COD m −2 d −1 . In anaerobic conditions only 4% of accumulated solids COD was biodegradable at maximum rates of 0.2–0.8 g COD m −2 d −1 . Thus, promoting aerobic conditions prevents clogging. HC was approximately 16% lower in planted units than in the unplanted unit while a similar drainable porosity drop (13–18%) was registered. The results showed that the presence/absence of vegetation and plant species did not significantly affect clogging in HSSF CWs. Highlights: Long-term clogging was assessed in unplanted/planted (4 different species) HSSF CWs. The presence of vegetation and plant species did not significantly affect clogging. Lower hydraulic conductivity but similar porosity in planted vs unplanted units. Solids biodegradation rate was 10–20 folds higher in aerobic vs anaerobic conditions. Promoting aerobic conditions prevents solids accumulation and clogging.